The physical rehabilitation in the early postoperation period with blocked femoral nailing - Nikitina O.V (Kharkov National Pedagogical University, 2010)
The system of rehabilitation measures of patients is resulted in an early postoperation period at the closed breaks of thigh. 24 patients took part in research. Age of patients were 15-56 years. Women there were 6 (25%) sufferings men 18 (75%). The sequence of employments is described by a medical physical culture, the complex of exercises is presented. A complex of rehabilitation measures must be dynamic with the gradual increase of the physical loading and account of features of concrete clinical case.